Prosecuting Gender-Based Violence in Armed Conflicts: Examining the Gendered Nature in Armed Conflicts - Khetarpal, Ms. Mahima; Sharma, Ms. Anubhuti (Trinity Law Review, 2026)
Gender-based violence (GBV) in armed conflict has emerged as a significant and complex issue within the realm of international humanitarian law (IHL). This paper explores the gendered nature of war crimes, with a focus on the prosecution and accountability of gender-based violence (GBV) during armed conflicts. Traditionally, war crimes prosecutions revolve around the acts of violence such as murder, torture and destruction of property. However in recent years, there has been increasing recognition of the prevalence of gender-specific atrocities, including sexual violence, forced prostitution and trafficking, which are often used as tools of war to humiliate, dominate and destroy communities.The paper critically examines the legal frameworks for addressing these forms of violence, highlighting key International Conventions such as the Geneva Conventions, the Rome Statute of the International Criminal Court (ICC), and the UN Security Council Resolutions on women, peace and security (particularly UNSCR 1325). It explores the challenges in prosecuting gender-based violence, including the complexities of evidence collection, victim protection and gendered biasness within legal institutions. Furthermore the paper addresses the intersectionality of GBV and recognizing how ethnicity, race and social status influence the experience and recognition of these crimes in conflicted areas.Drawing on case studies from post-conflict tribunals, such as the International Criminal Tribunal for the former Yugoslavia (ICTY) and the International Criminal Tribunal for Rwanda (ICTR) this paper highlights both successes and shortcomings in the legal prosecution of gender-based war crimes. In doing so, it underscores the need for a more robust and gender-sensitive approach to both the legal prosecution of GBV and the broader discourse of accountability and justice in post-conflict societies. At the end this paper argues that addressing the gendered nature of war crimes is essential for achieving meaningful justice for victims and for the prevention of sexual and gender-based violence in future conflicts.
Keywords: frameworks; conflicts; humiliate